2017
DOI: 10.1016/j.appet.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The bogus taste test: Validity as a measure of laboratory food intake

Abstract: Because overconsumption of food contributes to ill health, understanding what affects how much people eat is of importance. The ‘bogus’ taste test is a measure widely used in eating behaviour research to identify factors that may have a causal effect on food intake. However, there has been no examination of the validity of the bogus taste test as a measure of food intake. We conducted a participant level analysis of 31 published laboratory studies that used the taste test to measure food intake. We assessed wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(113 citation statements)
references
References 89 publications
3
109
1
Order By: Relevance
“…Importantly, intended consumption in this study positively correlated with factors known to predict actual eating, such as hunger and liking (e.g., Robinson et al, 2017). In line with previous work (e.g., Wilkinson et al, 2012), it is argued that the measure of intended consumption in the present study is likely to map well onto actual consumption.…”
Section: Limitations and Future Researchsupporting
confidence: 88%
“…Importantly, intended consumption in this study positively correlated with factors known to predict actual eating, such as hunger and liking (e.g., Robinson et al, 2017). In line with previous work (e.g., Wilkinson et al, 2012), it is argued that the measure of intended consumption in the present study is likely to map well onto actual consumption.…”
Section: Limitations and Future Researchsupporting
confidence: 88%
“…The bogus taste test is a validated measure of eating behaviour used to test the effect of experimental factors on the consumption of palatable food 30 . In the present study, each participant was presented with three types of food, each of which was contained in a standardised white ceramic bowl.…”
Section: Methodsmentioning
confidence: 99%
“…The form of the taste test is commonly used in the eating literature and has been demonstrated to be a reliable metric for food consumption. Prior validation studies have shown variability in this kind of paradigm to be responsive to food palatability and level of hunger [22], and responsive to acute manipulations of executive function using cTBS targeting the left dlPFC [3,23]. Participants were given condition specific instructions during the lead-in to the taste test: participants in the facilitation condition were instructed to "eat as much as you like in order to make your ratings" while those in the inhibition condition were instructed to "eat the bare minimum in order to make your ratings.…”
Section: Food Consumptionmentioning
confidence: 99%